The effect of food intake on the pk of rhein released from diacerein - Ming Huang; Shun-lin Zong; Quan-ying Zhang (Brazilian Journal of Pharmaceutical Sciences, 2020)
Diacerein is a symptomatic slow-acting drug used for treating osteoarthritis. This drug is completely metabolized into the active metabolite rhein before reaching the systemic circulation. This study evaluated the effects of food on the pharmacokinetics of rhein released from diacerein in healthy Chinese subjects. This was a single-center, randomized, single-dose, open-label, two-period, cross-over study. Twenty-four healthy subjects were randomly selected to receive a single oral dose of 50 mg diacerein capsule in either fasted or fed state on two separate visits. Plasma samples were analyzed with LC-MS/MS. Pharmacokinetic parameters were calculated using WinNonlin software. In the fasted and fed states, the main pharmacokinetic parameters of diacerein capsule were as follows: Cmax were (4471 ± 936), (3225 ± 755) ng/mL, t1/2 were (4.22 ± 0.42), (4.19 ± 1.05) h, tmax were (2.61 ± 1.25), (3.81 ± 1.29) h, AUC0-24 h were (24223 ± 4895), (24316 ± 5856) h·ng/mL, and AUC0-∞ were (24743 ± 5046), (25170 ± 6415) h·ng/mL. The absorption rate of diacerein capsule was obviously delayed by food intake but the absorption degree remained unaffected.